Strategic directions for improving the administrative and legal regulation of the activities of law enforcement agencies as subjects of the formation and implementation of state policy in the field of national security and defense - MAKARCHUK, Vitalii (Economics Finances Law, 2024)
Introduction. Law enforcement agencies as subjects of formation and implementation of state policy in the field of national security and defense must have an appropriate organizational and legal framework for carrying out their activities. This involves two separate important directions of optimization of the current process of administrative and legal regulation of their activities, which is collectively objectified by the need to review scientific and normative discourses regarding the place and role of law enforcement agencies in the mechanism of ensuring national security of Ukraine. The purpose of the paper is to analyze the strategic directions of improving the administrative and legal regulation of the activities of law enforcement agencies as subjects of the formation and implementation of state policy in the field of national security and defense. Results. Since law enforcement agencies in the researched area are generally divided into those that are independent or structural within the representative body - the Ministry of Internal Affairs of Ukraine, we believe that the formation of a separate independent authority in the proposed context is generally inappropriate, as well as the granting of such powers to already existing ones. Conclusions. Law enforcement agencies should be provided with the ability to effectively influence various aspects of the country's security from the position of functional unity, which will allow them to strategically and functionally solve issues of national security and defense of Ukraine. We have proposed an author's variation of improving the administrative and legal regulation of the activities of law enforcement agencies as subjects of the formation and implementation of state policy in the field of national security and defense with emphasis on the need to create a specialized state entity - the Center for Coordination and Interaction of Law Enforcement Activities under the National Security and Defense Council of Ukraine, which will represent the institute of law enforcement activities in Ukraine.